Strategi Pengembangan Potensi Agrowisata Leuweung Tiis Desa Trunamanggala - Siti Meisya Maulida; ⁠Irena Novarlia; Oman Sukirman (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The development of agro-tourism is one of the sustainable developments in the agricultural industry that can increase various potentials in the agricultural industry and improve the economy through tourism activities. Developing agro-tourism, of course, requires the right strategy, in this study an analysis of the potential owned by Leuweung Tiis Agrotourism, Trunamanggala Village, by identifying internal environmental factors and external environmental factors, with to produce alternative strategies to develop the potential of Leuweung Tiis Agrotourism. The research uses qualitative methods by conducting observations and interviews with parties involved in the development of Leuweung Tiis Agrotourism. The data analysis method used is SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis. The results of the analysis show that the current position of Leuweung Tiis Agrotourism is in quadrant II, which means that it has strong internal strength but is faced with various threats. An alternative priority strategy that can be applied is the S-T (Strengths-Threats) strategy by developing the current potential,building new attractions following the concept of agrotourism and the developing owned commodities, supported by adequate facilities and accessibility to provide comfort to tourists. In addition, taking advantage of support from the government to improve the quality of human resources of the surrounding community to encourage the strategy of developing the potential of Leuweung Tiis Agrotourism in the future.